(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Biosensor for measuring bacterial concentrations for use biotechnology and the health sciences would allow a rapid, robust and sensitive real-time monitoring of bacteria. Kim et al [1] has developed such a method using impedance spectroscopy, and was able to measure in real-time the concentration of E. coli at 0.01 MHz frequency using impedance changes. We modeled the growth kinetics using several nonlinear regression methods and discovered that the modified Gompertz model is the best model for the growth of the bacterium [2]. Bacterial growth curves are time-dependent series model and the use of nonlinear regression method relies heavily on the assumption that the residuals must not show autocorrelation. If this assumption is satisfied than the test is said to be robust. In this work we perform statistical diagnosis test to test for the presence of autocorrelation in this model and found out its absence suggesting that the model is robust enough and adequate.